Strategic Organizational Performance at Electric Company in Indonesia - Rio Afrianda; Veithzal Rivai Zainal; Indra Siswanti (Universitas Mercu Buana, 2023)
The goal of the study is to examine how organizational performance is impacted by transformational leadership and strategic organizational change management, with organizational environment serving as a mediating element in Indonesia's electricity state-owned enterprises. This is a quantitative, non-experimental study conducted between October 2022 and January 2023 in the divisions of PLN Head Quarter, as well as its subsidiaries and affiliates, with 1.429 respondents. SPSS and LISREL are used to do the analysis. According to research, both strategic organizational change management and transformational leadership styles have a positive and significant impact on organizational climate, with strategic organizational change management having the most significant impact. Organizational climate, strategic organizational change management, and transformational leadership all have a positive and significant impact.